Developing an e-Community Approach to Community Services in Kitigan Zibi Anishinabeg First Nation - Whiteduck, Gilbert; Tenasco, Anita; O'Donnell, Susan; Whiteduck, Tim; Lockhart, Emily (University of Waterloo Library, 2013)
Kitigan Zibi Anishinabeg First Nation is a leader in community and social services. This rural First Nation – the largest Algonquin community in Canada - has since 1980 successfully supported community members to take ownership of service development and delivery. They have made many services and programs available to community members, including: an elementary and secondary school, a day-care, a community hall, a community radio, a health centre, a police department, a youth centre, and others. Their community services are led and staffed by fully trained and qualified community members. As computers, broadband internet and cellular services have become available in Kitigan Zibi, the service sectors have been integrating these technologies with a goal of improving services for and communications with community members. However they face many challenges in their efforts to remain innovative and plan for future delivery of services using technologies. Our study, based on qualitative analysis from interviews with 14 community services staff in Kitigan Zibi, will explore their current successes, challenges, and future potential for integrating information and communication technologies (ICT) into services that promote community and social development. The analysis discusses the eCommunity approach advocated by the Assembly of First Nations.